Ethical Drivers of Environmentally Responsible B2B Purchasing: An Empirical Research in the Swedish Food Retail Industry - Arash KORDESTANI1; Kaveh PEIGHAMBARI2; Setayesh SATTARI3 (Communications of International Proceedings, 2025)
Businesses play a central role in addressing environmental sustainability, and one of their most difficult internal decisions is whether to commit to environmentally responsible purchasing. This study develops a theoretical framework to explain what drives purchasing professionals in Sweden’s food retail industry to engage in environmentally responsible purchasing. The study addresses a gap in the literature, where most prior research has examined sustainable purchasing at the firm or supply chain level, while the role of individual buyers’ moral beliefs and their organizational context in B2B retail settings has received less attention. The framework is tested using survey data from 573 purchasing managers in the Swedish food retail sector, based on established measures of moral philosophy, ethical decision-making, attitudes and environmentally responsible purchasing behavior. The findings show that all proposed hypotheses are supported, indicating that moral beliefs, together with situational and organizational influences, play a key role in individuals’ environmentally responsible decision making within organizations. Together, these results highlight how companies can encourage environmentally responsible purchasing by supporting the moral beliefs of purchasers and the ethical influence of top managers and peers.
Keywords: Environmentally responsible purchasing; Moral philosophy; Food retail; Sweden